The role of total elbow arthroplasty in traumatology - Mansat, P.; Bonnevialle, N.; Rongières, M.; Bonnevialle, P. (Orthopaedics & traumatology, surgery & research, 2014)
Fractures of the distal humerus account for 5% of osteoporotic fractures in subjects older than 60 years. A history of osteoporosis, co-morbidities, and joint comminution make their management difficult. The therapeutic options are limited to functional treatments, osteosynthesis, or either partial or total arthroplasty. Functional treatment of distal humerus fractures in the elderly subject provide inconsistent results, often with persistence of pain with a stiff or unstable elbow. Osteosynthesis remains the reference treatment for these fractures, following the principle of stable and rigid osteosynthesis allowing early mobilization. However, joint comminution and a history of osteoporosis occasionally make it impossible to meet this objective, with a considerable rate of complications and surgical revisions. Total elbow arthroplasty remains an alternative to osteosynthesis with very satisfactory immediate results restoring a painless, stable, and functional elbow. These results seem reproducible and sustainable over time. The complication rate is not uncommon with an approximately 10% surgical revision rate. Elbow hemiarthroplasty remains to be validated in this indication. V.